Tinjauan Yuridis Terhadap Hukum Berdasarkan Hibah Akta Penyelesaian Sengketa Tanah (Studi Putusan Pengadilan Negeri Nomor: 54/Pdt. G/2021/Pn. Pwt) - Choliek, Vito Qobul (Proceedings Series on Social Sciences & Humanities, 2024)
A grant is a legal action that aims to transfer ownership rights to another party. Grants can only be made to objects that already exist at the time of the grant. Grant problems are still the cause of disputes in the community, the result of grant problems is the lack of an authentic grant deed owned by the grantee or the lack of understanding of the difference in strength between grant and inheritance deeds, especially an object that is granted in the form of a plot of land. Land disputes related to grant deeds are generally a frequent conflict. The parties to the dispute are mostly individuals, which allows land disputes to cause losses for one of the parties to the dispute and does not rule out the possibility of bearing the most severe consequences. The purpose of this writing is to be able to know and understand the factors that cause unlawful acts committed as well as the legal review of decision Number. 54/Pdt. G/2021/Pn. Pwt. The formulation of the problems that arise in this writing is about how the factors that cause unlawful acts committed and how the legal review of decision Number. 54/Pdt. G/2021/Pn. Pwt. This writing is done using the normative juridical method through law and conceptual. In this study the authors used primary legal materials that are binding and secondary legal materials as references. The results of this study are about the factors that cause unlawful acts committed and the legal review of decision Number. 54/Pdt. G/2021/Pn. Pwt.